2020
DOI: 10.1038/s41392-020-00286-5
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord-derived mesenchymal stem cell therapy in patients with COVID-19: a phase 1 clinical trial

Abstract: No effective drug treatments are available for coronavirus disease 2019 (COVID-19). Host-directed therapies targeting the underlying aberrant immune responses leading to pulmonary tissue damage, death, or long-term functional disability in survivors require clinical evaluation. We performed a parallel assigned controlled, non-randomized, phase 1 clinical trial to evaluate the safety of human umbilical cord-derived mesenchymal stem cells (UC-MSCs) infusions in the treatment of patients with moderate and severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
283
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(289 citation statements)
references
References 28 publications
4
283
0
2
Order By: Relevance
“…Due to the small sample size, there was no comparative analysis between the two groups, but the patients in the MSCs group displayed a reduction of serum IL-6. Moreover, this trial demonstrated that transplantation of MSCs in patients with COVID-19 was safe and no serious adverse events were reported (Meng et al, 2020). In addition, a case report has described the clinical application of human umbilical cord-derived MSCs in a patient with severe COVID-19 pneumonia, who was intravenous injected with 1 × 10 6 cells/kg.…”
Section: Clinical Application Of Mscs For Covid-19mentioning
confidence: 79%
“…Due to the small sample size, there was no comparative analysis between the two groups, but the patients in the MSCs group displayed a reduction of serum IL-6. Moreover, this trial demonstrated that transplantation of MSCs in patients with COVID-19 was safe and no serious adverse events were reported (Meng et al, 2020). In addition, a case report has described the clinical application of human umbilical cord-derived MSCs in a patient with severe COVID-19 pneumonia, who was intravenous injected with 1 × 10 6 cells/kg.…”
Section: Clinical Application Of Mscs For Covid-19mentioning
confidence: 79%
“…Surprisingly, the pangolin coronavirus of GX_P2V could not only infect human mature somatic cells 1 , but also infect the hESCs, endoderm, ectoderm, hAFECs and hLPCs, indicating the possibility of the cross-species transmission and potential danger of coronavirus from animals. However, both viruses could not infect mesoderm, even though it expresses viral recptor of ACE2 and TMPRSS2, indicating the potential inhibitory activity of mesoderm to these coronaviruses, which may explain why mesenchymal stem cells could be used as a therapy tool for COVID-19 treatment 15 . The potential consequence of SARS-CoV-2 and animal coronavirus such as GX_P2V infection in hESCs, germ layer and induced progenitors should be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous and allogenic MSC therapy has emerged as inhibiting of the immune system and thus treating COVID-19 pneumonia [ 13 , 14 , 21 ]. Assessing safety and efficacy of UC-MSCs in treating the pneumonia associated to the viral infection represents the major objective of these clinical trials [ 160 – 163 ]. UC-MSCs are also used in treating pneumonia in patients infected with coronavirus [ 164 , 165 ].…”
Section: Refining New Cell-based Therapies In the Context Of Covid-19mentioning
confidence: 99%
“…First published results with infused umbilical cord MSCs (UC-MSCs) to critically ill COVID-19 patients present an improved therapeutic outcome [ 156 , 162 , 163 ]. Other strategies consisted of using ACE2 − UC-MSCs leading to an improved pulmonary functional activity and absence of SARS-CoV-2 nucleic acid with more benefit to elderly patients [ 148 ].…”
Section: Refining New Cell-based Therapies In the Context Of Covid-19mentioning
confidence: 99%